Inorganic porous ultra-light spherical particle material as well as preparation method and application thereof

Through the combined structure of the core particles and cladding layer of the inorganic porous ultra-light spherical microparticle material, the problems of low strength and poor dispersion of vitrified micro-perlite are solved, and high compression resistance, low density and good fluidity are achieved. Stomatal spherical particles, suitable for petroleum cementing and many other applications.

CN119263790APending Publication Date: 2025-01-07ANHUI JUBO NEW MATERIAL TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411376005.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The vitrified micro-perlite in the existing petroleum cement cement lightening materials has low strength, high density and poor dispersion, resulting in poor use effect and poor hydrophilic performance, which is prone to stratification.

Method used

Using inorganic porous ultralight spherical microparticle material, the design of the intermediate mixed transition layer through the combined structure of core particles and cladding layer is controlled to foam the core particles and seal it by the cladding layer, forming high compression resistance, Low-density and good fluidity micro-porous spherical particles.

Benefits of technology

It has achieved inorganic porous ultra-light spherical particles with high compressive strength, low density, good fluidity, high temperature resistance, low water absorption and corrosion resistance. It is widely used in petroleum cementing, insulation, fireproof, heat insulation, sound absorption, sound insulation and other fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of an inorganic porous ultra-light spherical particle material, which comprises the following steps: weighing preparation raw materials of core particles according to a mass ratio, mixing the preparation raw materials of the core particles, grinding, adding the ground material into a granulator, and granulating to obtain granules; weighing raw materials for preparing the coating layer according to the mass ratio, mixing the raw materials for preparing the coating layer, and grinding to prepare coating slurry; coating the granules with the coating slurry, and then drying the coated granules; and putting the dried coated granules into a calcining furnace for calcining, wherein the calcining temperature is between the melting temperature of the core granules and the melting temperature of the coating layer. According to the method, firstly, the core particles are melted and foamed to generate gas, the coating layer can seal pores of foaming balls of the core particles during calcination, meanwhile, micropores are generated in the surface of the coating layer in the calcination process, and finally the melted and wrapped porous ultra-light spherical microparticles with the micropores in the surface are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic particle materials, and particularly relates to an inorganic porous ultra-light spherical particle material and a preparation method and application thereof. Background Art

[0002] At present, the most effective lightening material for petroleum cementing is glass beads, but due to the high price, most of them use vitrified micro-beads and perlite. The biggest drawback of vitrified micro-beads and perlite is its low strength, which leads to a large density difference during use and poor use effect. At the same time, due to the poor hydrophilicity of the above two materials, they have poor dispersibility during use and are prone to stratification, which affects the use effect. Summary of the invention

[0003] The purpose of the present invention is to provide an inorganic porous ultra-light spherical particle material and its preparation method and application, which can produce an inorganic porous ultra-light spherical particle material with high compressive strength, high floating rate, low density, good fluidity, high temperature resistance, low water absorption, easy drainage and corrosion resistance. So that it can be widely used in the fields of oil well cementing, thermal insulation, fireproof, heat insulation coating, sound absorption, sound insulation, energy-saving building materials, etc.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is:

[0005] An inorganic porous ultra-light spherical particle material, the inorganic porous ultra-light spherical particle material comprises a core particle and a coating layer, the core particle comprises SiO 2 :60~78%、Al 2 O 3 : 3~18%, CaO: 7~15%, MgO: 1~5%, K 2 O: 1-6%, Na 2 O: 0.1~12%, B 2 O 3 :0~3%、Fe 2 O 3 :0.1~1%、ZnO:0~1.5%;The coating layer comprises SiO 2 :55~75%、Al 2 O 3 : 10~40%, CaO: 0.5~10%, MgO: 0.1~2%, K 2 O: 0.1~4%, Na 2 O: 0.1~6%, B 2 O 3 :0~4%、Fe 2 O 3 :0.1~1%,

[0006] It also includes an intermediate melting transition layer, which is between the core particles and the coating layer. The intermediate melting transition layer is an intermediate layer formed by melting the core particles and the coating layer.

[0007] Preferably, the melting temperature of the core particle is lower than the melting temperature of the coating layer.

[0008] Preferably, the particle size of the inorganic porous ultra-light spherical particulate material is 0.1 mm to 5 mm.

[0009] Another aspect of the present invention provides a method for preparing the inorganic porous ultra-light spherical particulate material as described above, comprising the following steps:

[0010] S1. Weigh the raw materials for preparing the core particles according to the mass ratio, mix the raw materials for preparing the core particles, perform wet grinding or dry grinding, and then add the ground material to a granulator for granulation to obtain granules;

[0011] S2, weighing the raw materials for preparing the coating layer according to the mass ratio, mixing the raw materials for preparing the coating layer, adding water, putting them into a grinder for grinding, and preparing a coating slurry;

[0012] S3, using the coating slurry of step S2 to coat the pellets of step S1, and then drying the coated pellets, wherein the moisture content of the dried coated pellets is less than 2.0%.

[0013] S4, placing the coated pellets dried in step S3 into a calcining furnace for calcining, wherein the calcining temperature is between the melting temperature of the core particles and the melting temperature of the coating layer.

[0014] Preferably, in step S1, if wet grinding is performed, the raw materials for preparing the core particles are mixed, water is added, and the mixture is put into a grinder for grinding to obtain a slurry, wherein the addition ratio of the raw materials for preparing the core particles to water is 1:0.6-1.

[0015] Preferably, in step S1, the fineness of the slurry is 250 mesh, and the residue on sieve is ≤0.5%.

[0016] Preferably, step S1 further comprises the following steps: aging the slurry for 48 hours and then adding the slurry to a granulator for granulation.

[0017] Preferably, the granulator is a centrifugal atomizing granulator, and the slurry is added to the centrifugal atomizing granulator for granulation to obtain preliminary particles. If the particle size of the preliminary particles is sufficient, the next step is carried out. If the particle size of the preliminary particles is not sufficient, the preliminary particles are placed in a ball forming machine for strengthening and finishing into balls, and then dried after the balls are formed.

[0018] Preferably, in step S2, the addition ratio of the raw materials for preparing the coating layer to water is 1:0.5-0.9.

[0019] Preferably, in step S2, the coating slurry has a fineness of 325 mesh, a sieve residue ≤ 0.1%, and a relative specific gravity of 1.35 to 1.55.

[0020] Preferably, in step S1, the particle size of the granules is 0.08-3 mm, and in step S3, the thickness of the granules coated with the coating slurry is 0.01-1 mm.

[0021] Preferably, in step S3, the coating slurry of step S2 is coated on the pellets of step S1 using a rotary coating machine, the rotation speed of the rotary coating machine is 8-30 r / min, the atomization pressure of the coating liquid is 0.5-2 MPa, and the coating amount is 5-40% of the pellet mass.

[0022] Preferably, in step S4, the dried coated pellets are placed in a calcining furnace for calcining, and the sintered medium balls are added to the calcining furnace at the same time. The calcining furnace is a roller calcining furnace, the calcining time is 40 to 70 minutes, and the roller speed of the roller calcining furnace is 5 to 15 r / min.

[0023] Preferably, in step S4, the sintering temperature of the sintered medium ball is 200°C to 300°C higher than the sintering temperature of the coated granules, and the particle size of the sintered medium ball is 3 to 7 times that of the coated granules; the compressive strength of the sintered medium ball is 3 to 5 MPa; and the apparent density of the sintered medium ball is 0.5 to 0.7 times that of the coated granules.

[0024] Another aspect of the present invention provides an application of the inorganic porous ultra-light spherical particle material as a lightening material for petroleum cementing.

[0025] Another aspect of the present invention provides an application of the inorganic porous ultra-light spherical particle material as described above, using it as a sound absorbing material.

[0026] The present invention wraps core spherical particles with a lower melting point with a coating layer with a higher melting point, and controls the calcination temperature so that the calcination temperature is between the melting points of the core spherical particles and the coating layer. The core particles are first melted and foamed to generate gas and pores. The coating layer seals the pores of the foamed balls of the core particles during calcination, and seals the gas in the intermediate mixed melt transition layer, so that the volume of the foamed balls of the core particles increases by 1 to 3 times. At the same time, micropores are generated on the surface of the coating layer during the calcination process, so as to finally obtain melt-wrapped porous ultra-light spherical microparticles with micropores on the surface.

[0027] The present invention seals the surface pores of the foaming ball with core particles, which is beneficial to the growth of the foaming ball and increases the strength of the foaming ball.

[0028] The inorganic porous ultra-light spherical microparticle material prepared by the present invention has high compressive strength, high floating rate, low density, good fluidity, hydrophilic surface, high temperature resistance, low water absorption rate, easy drainage and corrosion resistance, so that it can be widely used in the field of oil well cementing, thermal insulation, fireproof and heat insulation coating.

[0029] On the other hand, because the product of the present invention has a large specific surface area and the surface of the spherical particles has a microporous structure, it can be used as a sound absorbing material. Of course, it is an ideal energy-saving space material in construction. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with specific embodiments.

[0031] The present invention provides a method for preparing an inorganic porous ultra-light spherical particle material, comprising the following steps:

[0032] S1, press SiO 2 :60~78%、Al 2 O 3 : 3~18%, CaO: 7~15%, MgO: 1~5%, K 2 O: 1-6%, Na 2 O: 0.1~12%, B 2 O 3 :0~3%、Fe 2 O 3 : 0.1-1%, ZnO: 0-1.5%, by mass ratio: weighing raw material powders for preparing core particles, mixing the raw material powders for preparing core particles for wet grinding or dry grinding, and then adding the ground material to a granulator for granulation to obtain granules;

[0033] Specifically, if wet grinding is performed, the raw material powders for preparing the core particles are mixed, water is added, and the mixture is put into a grinder for grinding to obtain a slurry, wherein the ratio of the raw material for preparing the core particles to water is 1:0.6-1; if dry grinding is performed, the raw material powders for preparing the core particles are mixed, the mixture is put into a grinder for grinding to obtain a grind, and the grind is put into a pelletizer, water is added for granulation, and the moisture content of the pellets after pelletization is 15-25%, and then the pellets are dried to make the moisture content of the pellets <5%.

[0034] More specifically, the coating-4 cup method is adopted, the viscosity of the wet-ground slurry is (coating-N) 40-80 seconds, the fineness is 250 mesh, and the sieve residue is ≤0.5%; after the slurry is aged for 48 hours, it is placed in a centrifugal atomization granulator for preliminary granulation, and the preliminary particle size is 0.05-0.5 mm. If the preliminary particle size meets the requirements, the next step is carried out. If the preliminary particle size is not enough, it is placed in a ball forming machine for strengthening and finishing into balls, and then dried to make the moisture content of the particles <5%. After screening, it is used for later use. The particle size of the particles out of the ball forming machine is 0.08-3 mm. The slurry is aged for 48 hours in order to improve the uniformity of the slurry.

[0035] S2, press SiO 2 :55~75%、Al 2 O 3 : 10~40%, CaO: 0.5~10%, MgO: 0.1~2%, K 2 O: 0.1~4%, Na 2 O: 0.1~6%, B 2 O 3 :0~4%、Fe 2 O 3 : 0.1-1%, by mass ratio, weigh the raw materials for preparing the coating layer, mix the raw materials for preparing the coating layer, add water, put them into a grinder for grinding, and prepare a coating slurry;

[0036] Specifically, the addition ratio of the raw materials for preparing the coating layer to water is 1:0.5-0.9, the coating slurry fineness is 325 mesh, the sieve residue is ≤0.1%, and the relative specific gravity is 1.35-1.55.

[0037] S3, using the slurry of step S2 to coat the pellets of step S1, and then drying the coated pellets;

[0038] Specifically, the screened core pellets and the coating slurry are placed in a rotary coating machine to coat the core pellets, with a coating layer thickness of 0.01 to 1 mm. The coating machine speed is 8 to 30 r / min, the coating liquid atomization pressure is 0.5 to 2 MPa, and the coating amount is 5 to 40% of the mass of the core particles. The coated pellet green body is dried by fluidized drying and can be put into a kiln for calcination, wherein the moisture content of the dried coated pellets is less than 2.0%.

[0039] S4, placing the coated pellets dried in step S3 into a calcining furnace for calcining, wherein the calcining temperature is between the melting temperature of the core particles and the melting temperature of the coating layer.

[0040] Specifically, according to the multi-component lowest eutectic point principle, the raw material ingredients for preparing the core particles will melt within the temperature range of 700°C to 1100°C and generate gas, and the raw material ingredients for preparing the coating layer will melt within the temperature range of 750°C to 1150°C. According to the specific raw material components for preparing the core particles and the raw material components for preparing the coating layer, the specific melting temperatures of the raw materials for preparing the core particles and the raw material temperatures for preparing the coating layer are obtained, and the calcination temperature is determined based on these two temperatures, wherein the calcination temperature is between the melting temperatures of the core particles and the coating layers, so that after the coated particles are calcined, the core particles melt but the coating layers do not melt.

[0041] The dried coated pellets are placed in a calcining furnace for calcining, and sintering medium balls are added into the calcining furnace at the same time. The calcining furnace is a roller-type calcining furnace, the calcining time is 40 to 70 minutes, the roller speed of the roller-type calcining furnace is 5 to 15 r / min, a continuous calcination method is adopted, and the heating method is electric heating; the atmosphere in the furnace maintains a slightly positive pressure, and the main purpose of the roller rotation of the roller-type calcining furnace is to stir during sintering. During stirring, the coated particles are isolated from each other by the sintering medium balls to avoid adhesion. At the same time, the coated pellets can be heated evenly, and the floating objects adhered to the surface of the coated pellets can also be ground off by the stirring medium.

[0042] More specifically, the sintering temperature of the sintered medium ball is 200°C to 300°C higher than the sintering temperature of the coated granules, and the particle size of the sintered medium ball is 3 to 7 times that of the coated granules; the compressive strength of the sintered medium ball is 3 to 5 MPa; the apparent density of the sintered medium ball is 0.5 to 0.7 times that of the coated granules. The sintered medium ball is a sintered spherical particle, and the material can be the same as that of the core particle or the coating layer.

[0043] Specifically, during the calcination process, the core particles in the coated granules are first melted and foamed to produce gas and pores. As the temperature rises, the coating layer seals the pores of the core particle foaming balls during calcination, and seals the gas in the intermediate mixed melt transition layer, so that the volume of the core particle foaming balls increases by 1-3 times. At the same time, micropores are generated on the surface of the coating layer during the calcination process, thereby finally obtaining melt-coated porous ultra-light spherical microparticles with micropores on the surface.

[0044] The final particle size is 0.1-5 mm, the thermal conductivity is 0.05-0.12 w / mk, the particle cylinder pressure strength is 2-8 MPa, and the density is 120-800 kg / m 3 ; Floating rate ≥ 90%; Hydrophilic particles have good dispersibility and are used as a lightening material for oil well cement. After the slurry is stirred at 12,000 rpm, at a pressure of 25 MPa and a temperature of 50°C, the density loss is less than 0.04 within 30 minutes.

[0045] S5. The spherical particles are put into the storage barrel for natural cooling. After cooling to room temperature, the sintering medium is separated first, and then screened, graded and packaged according to demand.

[0046] Another aspect of the present invention provides an application of the inorganic porous ultra-light spherical particle material as a lightening material for petroleum cementing.

[0047] Another aspect of the present invention provides an application of the inorganic porous ultra-light spherical particle material as described above, using it as a sound absorbing material.

[0048] The following are specific embodiments:

[0049] Example 1

[0050] S1. Weigh the raw materials for preparing the core particles according to the mass ratio. The raw materials for preparing the core particles are composed of: SiO 2 : 68%; AI 2 O 3 :8%; CaO: 9%; MgO: 2%; K 2 O: 5%; Na 2 O: 4%; B 2 O 3 :2%;Fe 2 O 3 :0.5%; ZnO:1.5%, the raw material powders for preparing the core particles are mixed, water is added and put into a grinder for grinding to obtain a slurry, wherein the addition ratio of the raw material for preparing the core particles to water is 1:0.6-1, the slurry fineness is 250 mesh, and the sieve residue is ≤0.5%; after the slurry is aged for 48 hours, it is put into a centrifugal atomization granulator for preliminary granulation, and the preliminary particle size is 0.05-0.5mm, and then it is put into a balling machine for strengthening and finishing into balls, and after drying and sieving, it is ready for use, wherein the particle size of the pellets out of the balling machine is 1.5-2.5mm, and the barrel pressure strength of the pellets is 0.5MPa;

[0051] S2. Weigh the raw materials for preparing the coating layer according to the mass ratio. The raw materials for preparing the coating layer are composed of: SiO 2 :61%;Al 2 O 3 :22%; CaO: 7%; MgO: 1.5%; K 2 O: 3.3%; Na 2 O: 2%; B 2 O 3 :3%;Fe 2 O 3 : 0.2%; after mixing the raw material powders for preparing the coating layer, add water and put them into a grinder for grinding to obtain a coating slurry, wherein the addition ratio of the raw material for preparing the coating layer to water is 1:0.6-1, the slurry fineness is 325 mesh, and the sieve residue is ≤0.1%;

[0052] S3. Put the screened core pellets and coating slurry into a rotary coating machine, coat the core pellets, the coating amount is 8% of the core particle mass, and then dry the coated pellet body through fluidized drying. The moisture content of the dried coated pellets is less than 2.0%.

[0053] S4, placing the coated pellets dried in step S3 into a roller calcining furnace for calcining, the maximum calcination temperature is 1050° C., and the calcination cycle is 55 minutes;

[0054] The performance of the obtained samples is as follows: particle size range 2-4mm; thermal conductivity coefficient 0.071w / mk; floating rate 98%; compressive strength 5.15MPa; density 330kg / m 3 Combustion performance A, can be used as lightweight sound-absorbing and heat-insulating panels for prefabricated buildings.

[0055] Example 2

[0056] S1. Weigh the raw materials for preparing the core particles according to the mass ratio. The raw materials for preparing the core particles are composed of: SiO 2 : 65%; AI 2 O 3 :10%; CaO: 10%; MgO: 1%; K 2 O: 6%; Na 2 O: 4%; B 2 O 3 :2%;Fe 2 O 3 :0.5%; ZnO:1.5%, the raw material powders for preparing the core particles are mixed, water is added and put into a grinder for grinding to obtain a slurry, wherein the addition ratio of the raw material for preparing the core particles to water is 1:0.6-1, the slurry fineness is 250 mesh, and the sieve residue is ≤0.5%; after the slurry is aged for 48 hours, it is put into a centrifugal atomization granulator for granulation, and is sieved for use, wherein the granule particle size is 0.12-0.21mm, and the granule cylinder pressure strength is 0.5MPa

[0057] S2. Weigh the raw materials for preparing the coating layer according to the mass ratio. The raw materials for preparing the coating layer are composed of: SiO 2 : 59%; AI 2 O 3 21%; CaO: 8%; MgO: 1.7%; K 2 O: 6%; Na 2 O: 4%; Fe 2 O 3: 0.3%, after mixing the raw material powder for preparing the coating layer, add water and put it into a grinder for grinding to obtain a coating slurry, wherein the addition ratio of the raw material for preparing the coating layer to water is 1:0.6-1, the slurry fineness is 325 mesh, and the sieve residue is ≤0.1%;

[0058] S3. Put the screened core pellets and coating slurry into a rotary coating machine, coat the core pellets, the coating amount is 18% of the core particle mass, and then dry the coated pellet body through fluidized drying. The moisture content of the dried coated pellets is less than 2.0%.

[0059] S4, placing the coated pellets dried in step S3 into a roller calcining furnace for calcining, the maximum calcination temperature is 950° C., and the calcination cycle is 50 min;

[0060] The properties of the obtained samples are as follows: particle size range 0.15-0.25mm; floating rate 95%; compressive strength 3.5MPa; density 720kg / m 3 As a lightening material, it is added to the cementing cement. After the slurry is stirred at 12,000 rpm, the density loss is less than 0.04 within 30 minutes at a pressure of 25 MPa and a temperature of 50°C. The setting strength after 48 hours is 10.3 MPa.

Claims

1. An inorganic porous ultra-light spherical particulate material, characterized in that: The inorganic porous ultra-light spherical particulate material includes core particles and a coating layer. The core particles contain, by mass%, 60-78% SiO2, 3-18% Al2O3, 7-15% CaO, 1-5% MgO, 1-6% K2O, 0.1-12% Na2O, 0-3% B2O3, 0.1-1% Fe2O3 and 0-1.5% ZnO; the coating layer contains, by mass%, 55-75% SiO2, 10-40% Al2O3, 0.5-10% CaO, 0.1-2% MgO, 0.1-4% K2O, 0.1-6% Na2O, 0-4% B2O3 and 0.1-1% Fe2O3.

2. The inorganic porous ultra-light spherical particulate material according to claim 1, characterized in that: The melting temperature of the core particle is lower than the melting temperature of the coating layer.

3. The inorganic porous ultra-light spherical particulate material according to claim 1, characterized in that: The particle size of the inorganic porous ultra-light spherical particle material is 0.1 mm to 5 mm.

4. A method for preparing the inorganic porous ultra-light spherical particulate material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Weigh the raw materials for preparing the core particles according to the mass ratio, mix the raw materials for preparing the core particles, perform wet grinding or dry grinding, and then add the ground material to a granulator for granulation to obtain granules; S2, weighing the raw materials for preparing the coating layer according to the mass ratio, mixing the raw materials for preparing the coating layer, adding water, putting them into a grinder for grinding, and preparing a coating slurry; S3, coating the pellets of step S1 with the coating slurry of step S2, and then drying the coated pellets; S4, placing the coated pellets dried in step S3 into a calcining furnace for calcining, wherein the calcining temperature is between the melting temperature of the core particles and the melting temperature of the coating layer.

5. The preparation method according to claim 4, characterized in that: In step S1, if wet grinding is performed, the raw materials for preparing the core particles are mixed, water is added, and the mixture is put into a grinder for grinding to obtain a slurry, wherein the addition ratio of the raw materials for preparing the core particles to water is 1:0.6-1.

6. The preparation method according to claim 5, characterized in that: The slurry has a fineness of 250 meshes and a sieve residue of ≤0.5%.

7. The preparation method according to claim 5, characterized in that: The following steps are also included: The slurry was aged for 48 hours and then added to the granulator for granulation.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The granulator is a centrifugal atomizing granulator. The slurry is added to the centrifugal atomizing granulator for granulation to obtain preliminary particles. If the particle size of the preliminary particles is sufficient, the next step is carried out. If the particle size of the preliminary particles is not sufficient, the preliminary particles are put into a balling machine for strengthening and finishing into balls, and then dried after the balls are formed.

9. The preparation method according to claim 4, characterized in that: In step S2, the addition ratio of the raw materials for preparing the coating layer to water is 1:0.5-0.

9.

10. The preparation method according to claim 4 or 9, characterized in that: In step S2, the coating slurry has a fineness of 325 mesh, a sieve residue of ≤0.1%, and a relative specific gravity of 1.35-1.

55.

11. The preparation method according to claim 4, characterized in that: In step S1, the particle size of the pellets is 0.08-3 mm, and in step S3, the thickness of the pellets coated with the coating slurry is 0.01-1 mm.

12. The preparation method according to claim 4, characterized in that: In step S3, the pellets of step S1 are coated with the coating slurry of step S2 using a rotary coating machine, the rotation speed of the rotary coating machine is 8-30 r / min, the atomization pressure of the coating liquid is 0.5-2 MPa, and the coating amount is 5-40% of the pellet mass.

13. The preparation method according to claim 4, characterized in that: In step S4, the dried coated pellets are placed in a calcining furnace for calcining, and sintered medium balls are added to the calcining furnace at the same time. The calcining furnace is a roller calcining furnace, the calcining time is 40 to 70 minutes, and the roller speed of the roller calcining furnace is 5 to 15 r / min.

14. The preparation method according to claim 13, characterized in that: In step S4, the sintering temperature of the sintered medium ball is 200°C to 300°C higher than the sintering temperature of the coated granules, and the particle size of the sintered medium ball is 3 to 7 times that of the coated granules; the compressive strength of the sintered medium ball is 3 to 5 MPa; and the apparent density of the sintered medium ball is 0.5 to 0.7 times that of the coated granules.

15. An application of the inorganic porous ultra-light spherical particulate material according to any one of claims 1 to 3, characterized in that: It is used as a lightening material for petroleum cementing.

16. An application of the inorganic porous ultra-light spherical particulate material according to any one of claims 1 to 3, characterized in that: Use it as a sound absorbing material.

Citation Information

Patent Citations

  • Process for firing pottery and ceramicite by reducing flame and kiln

    CN101200377A

  • Manufacturing method of expanded porous glass particles

    CN110183099A

  • High-strength microbead lightening material for oil well cement and preparation method of high-strength microbead lightening material

    CN117164263A

  • Highly strong inorganic foamed granule and its production

    JP1996253377A